2011
DOI: 10.2135/cropsci2010.10.0595
|View full text |Cite
|
Sign up to set email alerts
|

Divot Resistance Varies among Bermudagrass and Zoysiagrass Cultivars

Abstract: Divots created by a golf stroke are a natural occurrence on golf courses and the resistance of turf to divot injury is an important factor that should be considered when selecting a turfgrass. Therefore, the primary objective of this experiment was to quantify the divot resistance for various bermudagrass {Cynodon spp. Rich.) and zoysiagrass {Zoysia spp. Willd.) cultivars in a field experiment, with a secondary objective to compare evaluation methods for quantifying divot resistance. This study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…The cultivars Patriot, Riviera, Tifsport, and Tifway bermudagrass, and Meyer and Diamond zoysiagrass had the best ball lie in unmown conditions, while Palisades had the poorest ball lie in unmown conditions. These results along with data on traffic tolerance (40) and divot resistance (38) and recovery (39) will assist golf course superintendents in selecting cultivars of bermudagrass and zoysiagrass well-adapted for golf course fairways or tees that contain low clipping yields and scalping tendencies as well as a good golf ball lie in order to help to reduce plant growth regulator use, equipment wear, and labor and fuel costs associated with maintaining a golf course turf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivars Patriot, Riviera, Tifsport, and Tifway bermudagrass, and Meyer and Diamond zoysiagrass had the best ball lie in unmown conditions, while Palisades had the poorest ball lie in unmown conditions. These results along with data on traffic tolerance (40) and divot resistance (38) and recovery (39) will assist golf course superintendents in selecting cultivars of bermudagrass and zoysiagrass well-adapted for golf course fairways or tees that contain low clipping yields and scalping tendencies as well as a good golf ball lie in order to help to reduce plant growth regulator use, equipment wear, and labor and fuel costs associated with maintaining a golf course turf.…”
Section: Discussionmentioning
confidence: 99%
“…Across the transition zone and southern United States, bermudagrass is the most commonly used turfgrass on fairways and tees (24), and bermudagrass and zoysiagrass are adapted to the transition and warm humid, climatic zones (4). Bermudagrass and zoysiagrass are desirable species for golf course fairways and tees due to their deep rooting, disease resistance, recovery potential, drought, heat, wear, traffic, and low mowing height tolerance (3,38,39,40).…”
Section: Introductionmentioning
confidence: 99%
“…On golf courses, the removal of divots and recovery from divoting caused by golfers are important considerations. Trappe et al (2011b) found that more force was required to remove divots from zoysiagrasses and that the divots removed were smaller than from bermudagrasses. Recovery from divoting, however, was fastest in C. dactylon cultivars, although the recovery of the best zoysiagrass cultivars was equivalent to that of hybrid bermudagrass (Trappe et al, 2011a).…”
Section: Adaptation and Plant Development: Implications Of Species‐lementioning
confidence: 99%
“…Another aspect of divot management is the overall size and the frequency a divot is made, otherwise known as divot resistance (9). Little work has attempted to quantify divot resistance or combine divot recovery and resistance to quantify a divot fitness index for a particular turfgrass.…”
Section: Other Factorsmentioning
confidence: 99%